PENGARUH FREKUENSI PULSE PENGELASAN GTAW PADA ALUMINIUM ALLOY 6061 - Ari Wibowo; Nugroho Pratomo Aryanto; Cahyo Budi Nugroho; Muhammad Ismail (JURNAL INTEGRASI, 2019)
This paper describes the effect of pulse frequency on the properties of microhardness, porosity and macrostructure in GTAW welding. This study used alluminum 6061 as a base metal and without filler metal. Pulse frequency is varied from 0 Hz to 10 Hz. The macrostructure results showed the maximum penetration depth occured at pulse frequency 6 Hz, while the maximum penetration width occured when did not pulse frequency. Micro hardness testing showed that the maximum hardness occured at pulse frequency 6 Hz while the lowest hardness occured at pulse frequency 10 Hz. AA 6061 welding without metal filler produced porosity which can have an impact on the hardness of the weld metal.